PENGAMANAN DATA TEKS MENGGUNAKAN METODE DIGITAL SIGNATURE ALGORITHM (DSA) DAN ADVANCED ENCRYPTION STANDARD (AES) - Mhd Reza Alfani; Mhd Furqan; Yusuf Ramadhan Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: The issue of data security and confidentiality are two important aspects of an information system. This is closely related to how important the information is sent and received by interested people. Cryptography is a field of science that aims to maintain the confidentiality of messages from unauthorized parties. The cryptographic algorithm that will be used is the Digital Signature Algorithm (DSA) asymmetric cryptography algorithm and combined with the Advanced Encryption Standard (AES) symmetric algorithm. DSA as authentication using a hash function cannot perform encryption and decryption, with a combination of Advanced Encryption Standard (AES) cryptography to enable encryption and decryption. Advanced Encryption Standard (AES) is a block cipher algorithm and has a symmetrical nature that uses a symmetric key during the encryption and decryption process. The text file type to be used is in the format (*.xlsx). Files that have been encrypted still use the same extension as the previous file but cannot be opened. Encrypted files have a size change of 30%. The decrypted file is exactly the same as the initial file before the encryption process is carried out. Keywords: cryptography, digital signature algorithm, advanced encryption standard,                   text data Abstrak: Masalah keamanan dan kerahasiaan data merupakan dua aspek penting dalam sistem informasi. Hal ini erat kaitannya dengan pentingnya informasi yang dikirimkan dan diterima oleh masyarakat yang berkepentingan. Kriptografi merupakan bidang ilmu yang menjaga kerahasiaan pesan dari pihak yang tidak berkepentingan. Algoritma kriptografi yang akan digunakan adalah algoritma kriptografi asimetris Digital Signature Algorithm (DSA) dan dikombinasikan dengan algoritma simetris Advanced Encryption Standard (AES). DSA sebagai autentikasi menggunakan fungsi hash tidak dapat melakukan enkripsi dan dekripsi, dengan kombinasi kriptografi Advanced Encryption Standard (AES) agar dapat melakukan enkripsi dan dekripsi. Advanced Encryption Standard (AES) merupakan algoritma enkripsi blok dan memiliki sifat simetris yang menggunakan kunci simetris selama enkripsi dan dekripsi. Jenis file teks yang akan digunakan berformat (*.xlsx). File yang telah dienkripsi masih memakai ekstensi seperti file sebelumnya namun tidak dapat dibuka. File hasil enkripsi memiliki perubahan ukuran sebesar 30%. File hasil dekripsi sama persis seperti file awal sebelum dilakukan proses enkripsi. Kata kunci: kriptografi, digital signature algorithm, advanced encryption standard, data teks